Scleral tunneling combined with the Tenon’s capsule coverage in Glaucoma Drainage Valve surgery - Yihua Yao; Jinping Gong; Nuozhou Wu; Sinan Liu; Yan Lin; Qin Ye; Biting Zhou; Yihua Zhu; Xiaohui Wang (BMC Ophthalmology)
Abstract Objective To evaluate the clinical efficacy of an modified surgical technique using scleral tunneling and Tenon’s capsule for implantation of the Ahmed Glaucoma Drainage Valve (AGV) in refractory glaucoma. Methods This research involved the retrospective collection of data from 78 patients diagnosed with refractory glaucoma who underwent implantation of the AGV using a modified technique combining scleral tunneling with autologous Tenon’s capsule. The analysis focused on preoperative and 60-month postoperative indices, which included the surgical technique employed, intraocular pressure (IOP) measurements, the utilization of antiglaucoma medications, rates of surgical success, and the incidence of postoperative complications. Results The findings suggest that the modified surgical technique exhibited an accuracy in the placement of implants. It also achieved remarkable postoperative control of IOP. The average IOP of the enrolled patients decreased from a preoperative maximum of 44.5 mmHg to 18.62 mmHg at 60 months postoperatively. Additionally, the usage of antiglaucoma medications decreased from an average of 2.88 preoperative medications to 1.76 medications at 60 months postoperatively. The rates of surgical success were recorded at 85.90% at 12 months, 82.54% at 24 months, 76.60% at 36 months, 71.88% at 48 months, and 66.67% at 60 months following the surgical procedure. It is noteworthy that no severe complications, including drain valve exposure and endophthalmitis, were reported. Conclusions The modified AGV implantation technique effectively regulated IOP, reduced medication dependence, and minimized severe complications. However, limitations such as small sample size and lack of a control group necessitate further large-scale trials to confirm its efficacy.